Solvent Effects on Activity and Conformation of Plasminogen Activator Inhibitor-1 - Andreasen, P. A.; Egelund, R.; Jensen, S.; Rodenburg, K. W. (Thrombosis and Haemostasis, 1999)
We have studied effects of the solvent composition on the activity and the conformation of human plasminogen activator inhibitor-1 (PAI-1) from HT-1080 fibrosarcoma cells. Non-ionic detergents, including Triton X-100, reduced the inhibitory activity of PAI-1 more than 20-fold at 0° C, but less than 2-fold at 37° C, while glycerol partly prevented the detergent-induced activity-loss at 0° C. The activity-loss was associated with an increase in PAI-1 substrate behaviour. Evaluating the PAI-1 conformation by proteolytic susceptibility of specific peptide bonds, we found that the V8-proteinase susceptibility of the Glu332-Ser333 (P17-P16) bond, part of the hinge between the reactive centre loop (RCL) and β-strand 5A, and the endoproteinase Asp-N susceptibility of several bonds in the β-strand 2A-α-helix E region were increased by detergents at both 0 and 37° C. The susceptibility of the Gln321-Ala322 and the Lys325-Val326 bonds in β-strand 5A to papain and trypsin, respectively, was increased by detergents at 0° C, but not at 37° C, showing a strict correlation between proteinase susceptibility of β-strand 5A and activity-loss at 0° C. Since the β-strand 2A-α-helix E region also showed differential susceptibility to endoproteinase Asp-N in latent, active, and reactive centre-cleaved PAI-1, we propose that a detergent-induced conformational change of the β-strand 2A-α-helix E region influences the movements of β-sheet A, resulting in a cold-induced conformational change of β-strand 5A and thereby an increased substrate behaviour at low temperatures. These results provide new information about the structural basis for serpin substrate behaviour.